2010
DOI: 10.1021/jf102821h
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phthalate Migration from Plastic Containers to Packaged Cooking Oil and Mineral Water

Abstract: The migration of phthalates (PAEs), a class of typical environmental estrogen contaminants in food, from food packaging to packaged food attracts more and more attention worldwide. Many factors will affect the migration processes. The purpose of this study was to evaluate PAE migration from plastic containers to cooking oil and mineral water packed in authentic commercial packaging and stored under various conditions (different storage temperatures, contact times, and storage states (static or dynamic state)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 23 publications
1
42
0
1
Order By: Relevance
“…Thermal degradation data of PVC plasticized with ESO and SOPE showed that the T d of PVC blends increased from 249.4 to 265.9 C and 275. 7 C, the T g increased from 27.5 to 43 C and 49.8 C, respectively. It indicated that both of plasticizers could improve the thermal ability of PVC blends.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thermal degradation data of PVC plasticized with ESO and SOPE showed that the T d of PVC blends increased from 249.4 to 265.9 C and 275. 7 C, the T g increased from 27.5 to 43 C and 49.8 C, respectively. It indicated that both of plasticizers could improve the thermal ability of PVC blends.…”
Section: Discussionmentioning
confidence: 94%
“…Phthalates as the main plasticizer additives of PVC have been used around the world for years due to excellent plasticizing effect, but phthalates may migrate from PVC products to environments when the materials contact with biological fluids, which will take potential risks to human health when they are used in food packing, automotive products, insect repellents, blood storage bags, and medical devices. [6][7][8][9] And the raw materials of phthalate are petroleum, scarcity of petroleum resources and the rising cost of petroleum products have led to the increasing trend towards developing of alternate sources of materials for industrial uses.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed preparation procedure was described previously elsewhere [21]. A dense mat of PA6 nanofibers with a thickness ranging from 70 to 200 μm was collected on the aluminum, and the electrospun time was 2-6 h.…”
Section: Preparation Of Pa6/ppy Core-shell Nanofibers Matmentioning
confidence: 99%
“…Since electrospun nanofibers could be easily obtained as a form of membrane or mat, disks SPE based on electrospun nanofibers mat is a preferential format of device for large volume water sample pre-concentration. Our previous research using Nylon6 (PA6) electrospun nanofibers mat as disks SPE sorbent has demonstrated highly effective extraction for some non-polar and medium polarity compounds in aqueous samples [21][22][23][24][25][26]. The disks SPE not only possesses a larger specific surface and more active situs for adsorption resulting in good mass transfer performance, which is helpful to process large volume sample with higher flow rate to obtain better enrichment coefficient, but also facilitates the miniaturization of SPE devices allowing the use of a reduced sorbent bed mass and low consumption of solvents, which is in perfect harmony with new trend of sample preparation [27].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have described the migration of phthalate esters from flexible plastic polymers into food, especially oils and fatty foods because of the lipophilicity of the esters (Xu et al 2010;Z. Guo et al 2010;Fan et al 2012;Ji et al 2013).…”
Section: Introductionmentioning
confidence: 98%